Conductivity improvement of CR doped AL203 materials / Nurhanna Batar @ Badar … [et al.] - Batar @ Badar, Nurhanna; Kamarulzaman, Che Norlida; Abdul Aziz, Nor Diyana; Jasimin, Mawar Hazwani; Rusdi, Roshidah (Research Innovation Business Unit, 2014)
Al2O3 is highly important in many fields of electronics and engineering due to its excellent chemical stability, good mechanical properties, and relatively low manufacturing cost. It is known that Al2O3 is highly insulating with a large band gap of 8.8 eV. It is the choice insulator for magnetic tunnel junctions (MTJ), superconducting Josephson junctions (JJ) and metal oxide semiconductor (MOS). Not much work has been done on the electrical effect of substitutional doping of metal oxide insulators such as Al2O3. It is therefore interesting to study the effects of doping on the electrical characteristics of Al2O3. Al2-xCrxO3 (ruby) exist naturally in the earth’s crust and widely used for hydraulics, airflow filters, solid-state lasers, solar energy and is valued as a gemstone. A substitution reaction producing pure phase phases is not easy to achieve for this material due to the high formation temperature. It is known that Al2O3 is a very stable compound with high formation temperature of 2054 degree Celsius. Therefore, it will not be easy to synthesize pure and single phase Al2-xCrxO3 materials, unless a suitable synthesis method is used and the thermal annealing is done at the correct temperature. This work focuses on the substitution of Al with Cr to produce Al2-xCrxO3 materials (x = 0.1, 0.2, 0.3). A high Cr content in the synthesized Al2-xCrxO3 materials was achieved via a new synthesis route, the self propagating combustion method, for investigation of the effect of Cr substitution on the electrical, optical band gap and structural characteristics of the modified Al2O3 materials. Our combustion synthesis method has successfully yielded a higher Cr content of 6 to 26% in the Al2-xCrxO3 powders. This illustrates that the self propagating combustion method is a good synthesis method for producing doped Al2-xCrxO3 materials. This simplest method not only can produce high yield purity material, but cost of synthesizing also low and just used a few starting materials. The X-Ray diffraction (XRD) results showed that all the samples were pure and that Cr was successfully substituted in the crystal lattice. The cell parameters and volume are linearly dependent on the Cr content. AC impedance spectroscopy results show that conductivity of the Cr doped samples increase exponentially with Cr content. The conductivities of the Al2-xCrxO3 have been found to increase by the order of one in the highest Cr content sample, Al1.7Cr0.3O3. It is also found that as the Cr content increases, band gap values decreases. This is a new and novel finding. This is attributed to band gap narrowing of the Al2-xCrxO3 powders as obtained from UV-Visible spectrophotometric studies. The Al2-xCrxO3 substituted materials have band gaps of between 4.49 to 4.90 eV, making it usable as semiconductor materials.